HEALTHCARE SC DALAM DISASTER OPERATION DI INDONESIA: STATE OF THE ART - Yoga, Samana; Santoso, Amelia (Departemen Teknik Industri, Fakultas Teknik, Universitas Diponegoro, 2022)
Ketika terjadi bencana alam, korban baik yang meninggal, maupun yang selamat membutuhkan bantuan seperti makanan, air bersih, farmasi, tenda peralatan medis, dan tenaga medis. Saat terjadi bencana alam, bantuan untuk layanan kesehatan (healthcare) dapat dikategorikan menjadi relief goods, seperti barang medis dan service goods, seperti tim medis. Healthcare dalam kondisi normal berbeda dengan healthcare dalam kondisi bencana. Healthcare dalam kondisi bencana atau yang dikenal dengan healthcare dalam operasi kemanusiaan (humanitarian operation) memiliki sifat yang mendadak dan mendesak sehingga sulit untuk diprediksi. Operasi kemanusiaan pada umumnya membutuhkan jaringan supply chain (SC) yang terkait dengan healthcare, termasuk farmasi dan tenaga medis. Namun, tidak seperti healthcare pada umumnya, healthcare dalam operasi kemanusiaan memiliki sifat yang tiba-tiba dan mendesak, sehingga lebih sulit untuk diprediksi. Penelitian ini merupakan studi literatur terkait penelitian healthcare SC dalam operasi kemanusiaan. Penelitian-penelitian tersebut dikategorikan ke dalam tiga tema: healthcare, disaster, dan healthcare in natural disaster. Topik penelitian berisi Operation Management, Coordination Mechanism, Logistic Operation, Funding, Scheduling, Location Optimization, Performance, Procurement, Information Technology, Inventory Management & Control, Service Management, dan Strategy Management. Tipe dari metode penelitian berisi Optimization, Simulation, Case Study, Literature Review, Empirical Study, and Theory/Conceptual. Abstract[Title: Healthcare SC in Disaster Operation in Indonesia: State of the Art] When a natural disaster occurs, there are always casualties. Both the dead and the survivors need assistance such as food, clean water, pharmacy, tent, medical equipment, and medical personnel. When a natural disaster occurs, assistance for healthcare can be categorized into relief goods, such as medical goods and service goods, such as medical teams. Healthcare under normal conditions is different from healthcare in disaster conditions. Healthcare in a disaster condition or known as healthcare in humanitarian operation, has a sudden and urgent nature, making it difficult to predict. The humanitarian operation generally requires a supply chain (SC) network related to healthcare, including pharmaceuticals and medical personnel. However, unlike healthcare in general, healthcare in humanitarian operations has a sudden and urgent nature, making it more difficult to predict. This paper is a literature study related to research in healthcare SC in humanitarian operations and can be categorized into three themes: healthcare, disaster, and healthcare in a natural disaster. The topic research contains Operation Management, Coordination Mechanism, Logistic Operation, Distribution, Funding, Scheduling, Location Optimization, Performance, Procurement, Information Technology, Inventory Management & Control, Service Management, and Strategy Management The type of research methods contains Optimization, Simulation, Case Study, Literature Review, Empirical Study, and Theory/Conceptual.Keywords: disasters; emergency; healthcare; resource